Luis Felipe Alarco's philosophy of education - Carrera-Honores, Luis (2020)
The Peruvian philosopher Luis Felipe Alarco reflected in the field of philosophy of education on the difference between philosophy of education and the sciences of education, the educational reality, the elements of education as the educator, educating, educational content and the educational goal. Finally, he reflected on the didactic method. In addition, Alarco addressed the study of these educational issues from a dualistic psychology and from a teleological, phenomenological and Christian point of view.